ω_I, γ -continuous functions and weakly ω_I, γ -continuous functions - Carpintero, C.; Rosas, E.; Salas-Brown, M.; Vásquez, L. (Sarajevo Journal of Mathematics, 2024)
Using the ω_I, γ-closed sets defined in carpintero, we introduce the notions of ω_I, γ-continuous functions and weakly ω_I, γ-continuous functions. Characterizations and properties of this new class of functions are obtained and studied. 2010 Mathematics Subject Classification. 54C10, 54D10.